Pengaruh Ekspor,Investasi PMDN dan Investasi PMA Terhadap Kesempatan Kerja di Provinsi Jawa Barat Tahun 2007-2021 - Muhammad Zaky Agung; Dewi Rahmi (UNISBA Press, 2023)
Abstract. Employment is one of the problems that still occurs in West Java, this is due to the increasing number of population and workforce but not being matched by good employment opportunities The export sector has an important role in employment opportunities, exports as a proxy for economic openness where economic openness is a factor that can influence industrial competitiveness in Indonesia. With economic openness, it will be easier for foreign capital to enter Indonesia. (Maulana, 2018). The purpose of this research is to analyze and find out the effect of exports, domestic investment and foreign investment on labor in West Java Province in 2007-2021. This study uses secondary data obtained from the Central of Statistics (BPS). This data is time series data from 2007-2021 by applying the ordinary least squares (OLS) multiple linear regression analysis method. The results of this study show that: (1) the export variable has a positive and significant effect on the employment opportunity in West Java Province in 2007-2021. (2) the domestic investment variable has a positive and significant effect on the employment opportunity in West Java Province in 2007-2021.(3) the Foreign investment variable has a positive but not significant effect on the employment opportunity in West Java Province in 2007-2021. Abstrak Ketenagakerjaan menjadi salah satu masalah yang masih terjadi di Jawa Barat, hal ini disebabkan karena jumlah penduduk dan angkatan kerja yang kian meningkat tetapi tidak diimbangi dengan lapangan pekerjaan yang baik. Sektor ekspor memiliki peranan penting terhadap kesempatan kerja, ekspor sebagai proksi keterbukaan ekonomi yang dimana keterbukaan ekonomi adalah faktor yang dapat mempengaruhi daya saing industri di Indonesia. Adanya keterbukaan ekonomi maka aliran modal asing akan semakin mudah memasuki Indonesia.(Maulana,2018). Tujuan penelitian ini adalah untuk menganalisa dan mengetahui pengaruh ekspor, investasi PMDN dan investasi PMA terhadap tenaga kerja di Provinsi Jawa Barat tahun 2007-2021. Penelitian ini menggunakan data sekunder yang diperoleh dari Badan Pusat Statistik (BPS) data ini merupakan data time series dari tahun 2007-2021 dengan mengamplikasikan metode analisis regresi linier berganda ordinary least square (OLS). Hasil penelitian ini menunjukan bahwa:(1) variabel ekspor berpengaruh positif dan signifikan terhadap tenaga kerja di Provinsi Jawa Barat tahun 2007- 2021. (2) variabel investasi PMDN berpengaruh positif dan signifikan terhadap tenaga kerja di Provinsi Jawa Barat tahun 2007-2021.(3) variabel investasi PMA berpengaruh positif tetapi tidak signifikan terhadap tenaga kerja di Provinsi Jawa Barat tahun 2007-2021.